Performance Enhancement of Solar Photovoltaic Thermal Energy Collection (PV/T) System with W-Shaped Rib Rouhgness - Ali, Subhan; Uniyal, Vipin (Journal of Graphic Era University, 2023)
The purpose of this study is to investigate the possibility of improving electrical (cell) efficiency, thermal efficiency, and overall performance by adding w-rib roughness to the bottom of the absorber plate. the bottom of the absorber plate being given w-rib roughness. Based on a mathematical simulation of the PV/T system as a function of pertinent geometrical parameters, such as relative roughness pitch, relative roughness height, and angle of attack, as well as design parameters, such as temperature rise and insolation, the performance parameters—enhancement of electrical efficiency, thermal efficiency, and overall performance—have been assessed. The system was examined using this simulation in relation to important geometrical factors. The results show that adopting w-rib roughness yields a significant improvement over the performance metrics obtained using smooth absorber plates.